The Making of New Mobility Markets: Frameworks Proposal Considering People with Disabilities and Connected Autonomous Vehicles - Daniel Leite Mesquita; Elisa Guimarães Cozadi; Daniel Carvalho de Rezende (Revista Interdisciplinar de Marketing, 2024)
Connected and Automated Vehicles (CAVs) are a recent technology which could promote a major change within automotive industry, creating a new mobility market. This market could bring new possibilities in mobility for people with disabilities (PWDs). Therefore, this essay sought to elaborate frameworks which could initially characterize CAVs market considering the inclusion of PWDs. The frameworks were elaborated in two parts, both considering CAVS as a nascent market: i) The market practices, and ii) its framings or agencements. In this sense, practices should focus on structuring the exchanges and norms of this market (new transport business models and its regulations, such as a universal design for CAVs). We argue that representative practices (offering inclusive mobility, safety, freedom, and independence for PWDs), should guide this market. Also, a correct communication of the benefits and risks of CAVs must structure this market. As for the framings proposed, they must guarantee an inclusive market, as far as pacifying goods, and pricing, should consider different social contexts and PWDs demands. We also mention the importance of governments and scientific societies on providing information that could result on new rules for CAVs inclusive markets.